Rôles et transformations des organisations sociales dans la Bolivie d’Evo Morales : le cas des organisations de cocaleros - Marion Bouchaud (Nuevo mundo - Mundos Nuevos, 2013)
From the early eighties, coca-growers social organizations have taken the lead of peasant mobilizations in Bolivia. Therefore, they have sparked off the debate on the need for a “political instrument” for the indigenous-peasant movement and the creation of the MAS. As a structure particularly efficient to convey social protest to the political field and to conquer political power, the MAS has laid the foundations of a “governments of social movements”. In particular, a conclusive role has been handed out to the cocaleras organizations in terms of policy-making and implementation in the field of drug control and interdiction. Yet, due to the difficulties for the government to strike a balance between the organizations’ corporatist demands and the need for short-term results regarding drug control, tensions promptly appeared. Because it wants to spare its social basis, the government tries to handle carefully the conflicting interests at the expense of the implementation of a clear-cut coca strategy regarding the control of coca production.